The effect of bronze particles on the physical and mechanical properties of acrylonitrile-butadiene-styrene copolymer - (:unkn) unknown (TAYLOR & FRANCIS INC, 2007)
In this study, 5, 10, and 15 vol.% of bronze ( Cu- 10 wt.% Sn) powder on the physical and mechanical properties of Acrylonitrile-Butadiene- Styrene ( ABS) were investigated experimentally. After preparing metal- polymer matrix composites ( PMC) with a twin screw extruder and injection molding, fracture surface, the modulus of elasticity, yield and tensile strength, percentage elongation, Izod impact strength, hardness ( Shore D), melt flow index ( MFI), heat deflection temperature ( HDT), Vicat softening point, and glass transition temperature ( T-g) of each sample were determined. As compared to the unfilled ABS. It was found that by increasing the vol.% of bronze in ABS, yield and tensile strength, % elongation, Izod impact strength, MFI values decreased, while the modulus of elasticity, Shore D hardness, Vicat softening point, and HDT values increased.
Keywords: ABS; bronze powder; mechanical properties; metal-polymer composite; FILLED POLYPROPYLENE COMPOSITES; DENSITY POLYETHYLENE COMPOSITES; METAL POWDERS; CONDUCTIVITY; POLYMERS